Electrification: Impacts on Women's Lives in Hunza and Nagar - Yaseen, Rozmeen; Ahmed, Zubair; Ullah, Ehsan (Journal of Development and Social Sciences, 2025)
Electrification has a significant impact on women in every field. Electricity enables women to be more advanced and makes their lives easier by reducing their workload through technology. The study aims to explore the socio-economic impact of electrification on women in Hunza Valley. This study is qualitative, and the researcher used different qualitative tools, i.e., in-depth interviews and an interview guide. Purposive sampling was used by the researcher, and 25 women were interviewed during the fieldwork. The data of the present study were analyzed thematically, and different themes were present in the study. The findings of the study suggest that access to electricity changes the life of rural women in every field of life, such as access to electric gadgets, education, health, information, decision making, participation in income-generating activities, saved time and increased productivity, changes in developmental skills, and learning opportunities. Therefore, the process of electrification and tools linked with the electrification should be employed with modernized apparatus to facilitate women’s role in the workplace in Hunza, Gilgit Baltistan, with the aim to help enhance the well-being as well as the conditions of women.